The Slow Demise Of The Most Favoured Nation - Duffy, Frances Annmarie (Prophetic Law Review, 2021)
The Most Favoured Nation Treatment (MFN) is the founding principle of the General Agreement on Tariffs and Trade (GATT) and its successor The World Trade Organisation. Introduced in 1947 by the GAT, and re-affirmed in 1995 by the WTO, the MFN aimed to rid the world of discriminatory trade practices. This aspirational aim was to create a level playing field for all countries engaged in trade and create more opportunities for developing nations to trade with those already flourishing on the world trade stage. With normative research methodology, this article claims that MFN has never achieved this aim. It examines how the MFN has been eroded over time by exceptions to the MFN allowed by the GAT and the WTO. Preferential Trade Agreements and new trade initiatives such as The Regional Comprehensive Economic Partnership (RCEP) and The Belt and Road Initiative (BRI) are also evidence of more departures from the MFN as countries seek new vehicles for more effective trade. The article concludes that the MFN is becoming more and more irrelevant over time, and little can be done to revive it.Keywords: Free Trade Agreements; Most Favoured Nation Treatment (MFN); Preferential Trade Agreements; Plurilateral Trade AgreementsKehancuran Perlahan Asas Most Favoured NationsAbstrakAsas Most Favoured Nations (MFN) adalah prinsip dasar dalam General Agreement on Tariffs and Trade (GATT) dan penerusnya yaitu Organisasi Perdagangan Dunia (WTO). Diperkenalkan pada tahun 1947 oleh GATT, dan ditegaskan kembali pada tahun 1995 oleh WTO, MFN bertujuan untuk membersihkan dunia dari praktik perdagangan yang diskriminatif. Tujuan aspirasional ini adalah untuk menciptakan 'taman bermain' yang setara bagi semua negara yang terlibat dalam perdagangan internasional dan menciptakan lebih banyak peluang bagi negara-negara berkembang untuk memiliki hubungan perdagangan dengan negara-negara maju di panggung perdagangan dunia. Dengan metodologi penelitian normatif, artikel ini mengklaim bahwa MFN tidak pernah mencapai tujuan ini. Artikel ini mengkaji bagaimana MFN telah terkikis dari waktu ke waktu oleh pengecualian terhadap MFN yang diizinkan oleh GATT dan WTO. Perjanjian Perdagangan Preferensial dan inisiatif perdagangan baru seperti Regional Comprehensive Partnership Agreement (RCEP) dan Belt and Road Initiative (BRI) juga merupakan bukti adanya lebih banyak penyimpangan dari MFN karena negara-negara mencari alat baru untuk perdagangan yang lebih efektif. Artikel ini menyimpulkan bahwa MFN menjadi semakin tidak relevan dari waktu ke waktu, dan sedikit yang dapat dilakukan untuk menghidupkannya kembali.Kata Kunci: Perjanjian Perdagangan Bebas; Asas Most Favoured Nations; Perjanjian Perdagangan Preferensial; Perjanjian Perdagangan Plurilateral